Mengembangkan Jaringan Usaha Kecil untuk Menyediakan Kesempatan Kerja bagi Kaum Muda dan Individu Kurang Terampil: Implikasi dari Ajaran Pacem in Terris - Siyena Wee; Theresia Noiman Derung (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
This research aims to describe the development of small business networks as an effort to create jobs for the younger generation and low-skilled communities. Referring to the teachings of Pacem in Terris which emphasize social justice, human rights and economic prosperity, small businesses are seen as an effective solution in facing the challenge of unemployment, especially among these vulnerable groups. SME networks have the potential to provide training, employment opportunities and skills development that can increase individual competitiveness in the labor market. This article also explores the application of Pacem in Terris principles, particularly solidarity and cooperation between individuals and groups, in small and medium enterprise development policies and programs to create inclusive and sustainable employment opportunities. It is hoped that this research will provide insight for policy makers and practitioners in formulating more effective strategies to support economic empowerment and poverty alleviation through strengthening the SME sector.